1997
DOI: 10.1021/js9604467
|View full text |Cite
|
Sign up to set email alerts
|

Antitumoral Activity of Liposomes and Immunoliposomes Containing 5-Fluorouridine Prodrugs

Abstract: Liposomes and immunoliposomes containing cytotoxic agents may be highly efficacious in intracavity therapy of malignancies confined principally to the peritoneal cavity. To assess the feasibility of this locoregional treatment, we prepared two derivatives of 5-fluorouridine (5-FUR), a highly cytotoxic metabolite of 5-fluorouracile, and incorporated them into REV liposomes, prepared with the reverse phase evaporation method. Encapsulation efficiency, drug leakage, and stability were determined, and size analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 44 publications
0
31
0
1
Order By: Relevance
“…Fusion of the biological membrane or endocytosis may involve this inverted structure. Previous studies suggested the excellent ability to facilitate drug or gene delivery into cells by PE [27,28]. Another mechanism of PE uptake by cells may be the transbilayer internalization pathway [12].…”
Section: Discussionmentioning
confidence: 99%
“…Fusion of the biological membrane or endocytosis may involve this inverted structure. Previous studies suggested the excellent ability to facilitate drug or gene delivery into cells by PE [27,28]. Another mechanism of PE uptake by cells may be the transbilayer internalization pathway [12].…”
Section: Discussionmentioning
confidence: 99%
“…Quantification is finally achieved through measuring the absorbance of TNB −2 at 412 nm and by using a calibration curve. 38 …”
Section: Quantification Of Conjugates In Liposomes External Layermentioning
confidence: 99%
“…As an example, encapsulation of a series of 4-(N)-acylated prodrugs of gemcitabine in liposomes can be mentioned (10). However, many small water-soluble molecules, such as ara-C, a NA related to gemcitabine, and 5-fluorouridine, diffused rapidly through the liposome bilayer, thus limiting the shelf life and clinical usefulness of these liposomal drug formulations (11,12). These findings strongly suggest the need to develop a new efficient drug delivery system for NA.…”
Section: Introductionmentioning
confidence: 99%